1982
DOI: 10.1159/000153317
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Survey of an Isolated Community in Bali, Indonesia

Abstract: 316 adults and children from an isolated community of Bali, Indonesia, have been tested for 18 red cell enzyme systems controlled by 24 loci, and haemoglobin. 13 loci were invariant. The other 11 loci showed variations similar to those found previously in Southeast Asian populations. Of special interest is the occurrence of lactate dehydrogenase Calcutta-1 variants, indicating Indian gene admixture, and PGM92, indicating a Melanesian genetic component. A few individuals were CA1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…A very rare example of mutant distribution is illustrated by GclA12 and GclC1', because they are found in Indonesia (Bali) and India (Papiha, personal communication). Their presence in these two groups is in agreement with the tales and mythologies of the Balinese group, which indicate an Indian origin (Breguet et al, 1982b). That these mutants are also present in Europe constitutes an interesting genetic evidence of the Indo-European migrations.…”
Section: Anthropological Relationship Between Asian Groups and Amerinsupporting
confidence: 86%
See 1 more Smart Citation
“…A very rare example of mutant distribution is illustrated by GclA12 and GclC1', because they are found in Indonesia (Bali) and India (Papiha, personal communication). Their presence in these two groups is in agreement with the tales and mythologies of the Balinese group, which indicate an Indian origin (Breguet et al, 1982b). That these mutants are also present in Europe constitutes an interesting genetic evidence of the Indo-European migrations.…”
Section: Anthropological Relationship Between Asian Groups and Amerinsupporting
confidence: 86%
“…haplotype was detected in the community of Tenganam (Bali) (Breguet et al, 1982b). Ac-In the Gm system, the Gm1,17,23,5,10,11,13,14 cording to Schanfeld et al (1980), the Gml;17,-5,10,11,13,14 when associated with the Gm23 antigen is characteristic of the African populations.…”
Section: A Common Ancestor For African Andmentioning
confidence: 75%
“…There may be regional differences in the incidence of G6PD defi ciency. Brequet et al [24] also observed a high frequency of G d-(10.8%) in isolated popula tions of Bali compared to that in the east Bali nese (2%). The high incidence of G6PD defi ciency may be due to malarial endemicity in some rural areas of Indonesia.…”
Section: G6pd Variantsmentioning
confidence: 86%